Histology of "placoderm" dermal skeletons: Implications for the nature of the ancestral gnathostome. (2nd February 2013) - Giles, Sam; Rücklin, Martin; Donoghue, Philip C.J.
Abstract The vertebrate dermal skeleton has long been interpreted to have evolved from a primitive condition exemplified by chondrichthyans. However, chondrichthyans and osteichthyans evolved from an ancestral gnathostome stem‐lineage in which the dermal skeleton was more extensively developed. To elucidate the histology and skeletal structure of the gnathostome crown‐ancestor we conducted a histological survey of the diversity of the dermal skeleton among the placoderms, a diverse clade or grade of early jawed vertebrates. The dermal skeleton of all placoderms is composed largely of a cancellar architecture of cellular dermal bone, surmounted by dermal tubercles in the most ancestral clades, including antiarchs. Acanthothoracids retain an ancestral condition for the dermal skeleton, and we record its secondary reduction in antiarchs. We also find that mechanisms for remodeling bone and facilitating different growth rates between adjoining plates are widespread throughout the placoderms. J. Morphol., 2013. © 2013 Wiley Periodicals, Inc.